STRATEGI KEBERHASILAN PEMERINTAH DAERAH ROKAN HULU DALAM MENGEMBANGKAN BADAN USAHA MILIK DESA SUMBER REZEKI DESA KOTA RAYA KECAMATAN KUNTO DARUSSALAM TAHUN 2016 - Sri Damayanti; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Improve the financial capacity of village government in the administration of government and increase village income of rural communities through various economic activities if rural communities. Estabilished instituation namely village’s business entity (BUMDes) according to village’s needs and potential. BUMDes in Rokan Hulu regency are many that are progressing, especially the Sumber Rezeki’s BUMDes Kota Raya’s village. This BUMDes gets the first rank of the best BUMDes in Rokan Hulu of 2016. The regional government have to implement a strategy to improve the quality of village planning in each village so that the objectives of the formation of a BUMDes will be maximally achieved. The formulation of the problem in this research is how the success strategy of the Rokan Hulu regional government in the developing a village’s business entity Sumber Rezeki Kota Raya’s village Kunto Darussalam district in 2016? And how the impact of success BUMDes Sumber Rezeki as a best one BUMDes in Rokan Hulu in 2016?The purpose of this research is to knowing about success strategy of the Rokan Hulu regional government in the developing a village’s business entity Sumber Rezeki Kota Raya’s village Kunto Darussalam district in 2016 And the impact of success BUMDes Sumber Rezeki as a best one BUMDes in Rokan Hulu in 2016. This research use qualitative approach and type of research is descriptive. Data collection techniq are interview and documentation. Data analysis use qualitative analysis.The result of this research is strategy of the Rokan Hulu regional government in the developing a village’s business entity very welcome by administrator of Sumber Rezeki’s BUMDes. Besides accepting administrator also make use of regional government, strategy so that Sumber Rezeki’s BUMDes was advanced and gets first rank the best one BUMDes in Rokan Hulu at 2016. Than impact that was got by Sumber Rezeki as the best BUMDes is achieving the objectives of the formation the BUMDes according to Rokan Hulu’s regent regulation No. 64 in 2016 about implementation instructions of village’s business entity.Key word : Strategy, Regional Government, BUMDes